2016
DOI: 10.1007/s00894-016-2944-x
|View full text |Cite
|
Sign up to set email alerts
|

Homology modeling, docking, and molecular dynamics simulation of the receptor GALR2 and its interactions with galanin and a positive allosteric modulator

Abstract: Galanin receptor type 2 (GALR2) is a class A G-protein-coupled receptor (GPCR), and it has been reported that orthosteric ligands and positive allosteric modulators (PAMs) of GALR2 could potentially be used to treat epilepsy. So far, the X-ray structure of this receptor has not been resolved, and knowledge of the 3D structure of GALR2 may prove informative in attempts to design novel ligands and to explore the mechanism for the allosteric modulation of this receptor. In this study, homology modeling was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Their calculations showed that BMS‐986122 bound to a putative allosteric site (see above) and interacted with a Trp at the top of TM VII (Trp 7.35) to alter the conformation of this TM domain resulting in stabilization of the binding of the orthosteric ligand methadone as determined by its interaction with Asp 3.32 in the orthosteric pocket and destabilization of Na + ion binding as measured by the distance of this ion from Asp 2.50. Similarly, recent MD simulations of the galanin receptor identified a potential allosteric site involving TM domains 2 and 3 and extracellular loops 1 and 2 that the authors propose could disrupt Na + binding (Hui et al , ).…”
Section: Mechanism Of Allostery At Opioid Receptorsmentioning
confidence: 88%
“…Their calculations showed that BMS‐986122 bound to a putative allosteric site (see above) and interacted with a Trp at the top of TM VII (Trp 7.35) to alter the conformation of this TM domain resulting in stabilization of the binding of the orthosteric ligand methadone as determined by its interaction with Asp 3.32 in the orthosteric pocket and destabilization of Na + ion binding as measured by the distance of this ion from Asp 2.50. Similarly, recent MD simulations of the galanin receptor identified a potential allosteric site involving TM domains 2 and 3 and extracellular loops 1 and 2 that the authors propose could disrupt Na + binding (Hui et al , ).…”
Section: Mechanism Of Allostery At Opioid Receptorsmentioning
confidence: 88%
“…In particular, there is evidence found through literature mining (score = 0.004) indicating that galanin depletion from the hippocampus may contribute to the maintenance of seizure activity [ 21 ], as well as genetic evidence (score = 1.0) showing that a galanin loss-of-function mutation leads to epilepsy in humans [ 22 ]. Interestingly, a recent paper suggests GALR2 as a more suitable potential drug target to treat epilepsy [ 23 ], but this literature mining result is currently the only type of evidence supporting the GALR2-epilepsy association in the Open Targets Platform. As a result, the corresponding overall score is a relatively low 0.018 which corresponds to the 20th percentile (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel studies to map the binding sites at the receptor level by docking analysis and site-directed mutagenesis, TMD 3 , TMD 6 , and TMD 7 together with ECL 2 and ECL 3 in GalR1 were shown to be the key structures forming the binding pocket for galanin docking (40,47). However, only TMD 6 , TMD 7 , and ECL 3 were required for the assembly of binding pocket in GalR2 (39,46) and the same was also true for GalR3 but with additional involvement of TMD 3 (48). At the molecular level, Gly 1 , Trp 2 , and Tyr 9 in galanin have been reported to interact with Phe 115 in TMD 3 , Phe 282 in ECL 3 , and His 264 in TMD 6 of GalR1, respectively (47,49).…”
Section: Discussionmentioning
confidence: 99%
“…After sequence alignment of OPRL1 with GalR2/3 to remove the gaps in ECL 2/3 and ICL 3 followed by introduction of disulfide bond between the well-conserved Cys residues in TMD 3 and ECL 2 and "ionic lock" structure in DRY motif of TMD 3 , in silico modeling of GalR2/3 was conducted with simulation of the receptor embedding in an asymmetric POPC/POPE membrane bilayer (Figures 2A, C). During the process, the N-and Cterminals of GalR2/3 were omitted for structural simulation as suggested by previous reports for human GalR1-3 modeling (39,40), mainly due to (i) the short N-terminal of GalR1-3 has a high degree of sequence variations but with no notable secondary structures, and (ii) the C-terminal tail in general is not involved in the formation of binding pocket in GPCR. As shown in the energy-minimized models after optimization of backbone coordinates and placement of side chains, the seven a helixes of TMD 1-7 in mouse GalR2 (Figures 2A, C) and GalR3 (Figures 2B, D) can be clustered into a "compact core" with a central binding pocket typical of GPCR by counter-clockwise arrangement of TMD 1-7 when viewed from the extracellular side.…”
Section: Homologous Modeling Of Mouse Galr2/3 With Spx Docking By MD Simulationmentioning
confidence: 99%